Grapes and Wine 2022
DOI: 10.5772/intechopen.101314
|View full text |Cite
|
Sign up to set email alerts
|

New Insights about the Influence of Yeasts Autolysis on Sparkling Wines Composition and Quality

Abstract: Sparkling wines elaborated using the traditional method undergo a second fermentation in the bottle. This process involves an aging time in contact with the lees, which enriches the wine in various substances, especially proteins, mannoproteins and polysaccharides, thanks to the autolysis of the yeasts. As a result of this yeast autolysis, sparkling wines benefit from better integration of carbon dioxide and a clear sensory improvement, especially in the case of long aging. This chapter synthetizes the main re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The total proteins and total polysaccharide concentrations were lower in the sparkling wines inoculated with the GPY-grown yeast than in those inoculated with the pied de cuveprepared yeast, although only the polysaccharide content showed significant differences (Table 2). The proteins and polysaccharides in the sparkling wines came from the base wine and the cellular autolysis [43]. If we bear in mind that the base wine was the same, then the differences found in the protein and polysaccharide contents in wines would likely be due to distinct autolysis degrees of yeast prepared by differing procedures.…”
Section: Parameters Related To Yeast Autolysis and Foaming Propertiesmentioning
confidence: 99%
“…The total proteins and total polysaccharide concentrations were lower in the sparkling wines inoculated with the GPY-grown yeast than in those inoculated with the pied de cuveprepared yeast, although only the polysaccharide content showed significant differences (Table 2). The proteins and polysaccharides in the sparkling wines came from the base wine and the cellular autolysis [43]. If we bear in mind that the base wine was the same, then the differences found in the protein and polysaccharide contents in wines would likely be due to distinct autolysis degrees of yeast prepared by differing procedures.…”
Section: Parameters Related To Yeast Autolysis and Foaming Propertiesmentioning
confidence: 99%
“…For instance, Pueyo et al [6] found that tartaric acid is positively correlated with the foam height. On the other hand, the visual properties of sparkling wines, such as the foam height and the foam persistence [7], represent the first attributes observed by consumers.…”
Section: Introductionmentioning
confidence: 99%